Shikimate Kinase (EC 2.7.1.71) from Mycobacterium tuberculosis: Kinetics and Structural Dynamics of a Potential Molecular Target for Drug Development - Saidemberg, D. M. [UNESP]; Passarelli, A. W. [UNESP]; Rodrigues, A. V. [UNESP]; Basso, L. A.; Santos, D. S.; Palma, Mario Sergio [UNESP] (Bentham Science Publ Ltd, 2011)
The enzymes of the shikimate pathway represent potential molecular targets for the development of non-toxic antimicrobial agents and anti-parasite drugs. One of the most promising of these enzymes is shikimate kinase (EC 2.7.1.71), which is responsible for the fifth step in the shikimate pathway. This enzyme phosphorylates shikimic acid to yield shikimate-3-phosphate, using ATP as a substrate. In this work, the conformational dynamics of the shikimate kinase from Mycobacterium tuberculosis was investigated in its apostate in solution. For this study, the enzyme was subjected to a gradient of temperatures from 15 degrees C to 45 degrees C in the presence or absence of deuterium oxide, and the amide H/D exchange was monitored using ESI-mass spectrometry. We observed: i) the phosphate binding domain in the apo-enzyme is fairly rigid and largely protected from solvent access, even at relatively high temperatures; ii) the shikimate binding domain is highly flexible, as indicated by the tendency of the apo-enzyme to exhibit large conformational changes to permit LID closure after the shikimate binding; iii) the nucleotide binding domain is initially conformationally rigid, which seems to favour the initial orientation of ADP/ATP, but becomes highly flexible at temperatures above 30 degrees C, which may permit domain rotation; iv) part of the LID domain, including the phosphate binding site, is partially rigid, while another part is highly flexible and accessible to the solvent.
Keywords: Tuberculosis; drug development; shikimate kinase; mass spectrometry; H/D exchange